PENYELESAIAN SENGKETA ANTARA NASABAH DAN BANK DALAM HUKUM PERBANKAN - Fitri, Sherly Nelsa; Nasawida, Metha Dian Puspa (Universitas Prof. Dr. Hazairin, SH, 2020)
This purpose of this researchfor knowing the ideal of Settlement Of Banking Dispute In Indonesia and practice princple of justice in law about Settlement Of Banking Dispute. This research used prespective normative and applied methods. This research used primary, and secondary legal materials. Legal material were collected through the study (library research), statute research, which theb analyzed using deductive. Result mediation procedure the ideal methods for Settlement Of Banking Dispute although for regulation banking law princple of justice in law has never been justice